PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSI DAN KECERDASAN SPIRITUAL TERHADAP KINERJA KARYAWAN PT. ANGKASA PURA II CABANG SSK II PEKANBARU - Rio Marpaung; Citra Rumondang (PEKBIS, 2014)
This research aims to identify and analyze the influence of intellectual intellegence,emotional intellegence and spiritual intellegence against employee’s performance atPT.Angkasa Pura II Branch of Sultan Syarif Kasim II Airport Pekanbaru. Thisresearch uses 74 people of sample which selected pursuant to of stratified simplerandom method. Research variable consist of intellectual intellegence, emotionalintellegence, and spiritual intellegence as independent variable, and also employeesperformance as dependent variable. The method of analysis used validity andreliability test, quantitative descriptive analysis method, partial and simultaneousanalysis (multiple liniar regression analysis with SPSS version 17.0).From theresult of this research, the simultaneous regression test showed that all theindependent variables had a significant influence on employee performancevariable. And partial regression test showed that variable partial intellectualintellegence, emotional intellegence, and spiritual intellegence have a significantinfluence on employee performance. Emotional intellegence have strongestinfluence to performance improvement. Analysis of the coefficient determination2produce value adjusted R = 0,619. This means that 61,9% change in the level ofinfluence employee performance is explained by change in the intellectualintellegence, emotional intellegence, and spiritual intellegence. While the remaining38,1% influenced by other variables which not examined in this research.Keywords: Intellectual Intellegence, emotional intelligence, spiritual intelligence,employee performance